Comparison of Classical Test Theory and Item Response Theory:A Review of Empirical Studies - Rahimah, Embong; Mustafa, Mamat; Ado Abdu, Bichi (2015)
Background: The practice of testing has become increasingly common and the reliance on information gained from test scores to make decision has made an indelible mark on our culture. The entire educational system is today highly concerned with the design and development of the tests, the procedures of testing, instruments for measuring data, and the methodology to understand and evaluate the results. In theory of measurement in education and psychology there are two competing measurement frameworks, namely Classical Test Theory (CTT) and Item Response Theory (IRT). The techniques of the two frameworks are applied in assessment situations to improve test analysis and test refinement procedures. Objective: The main purpose of this paper is to provide a critical review of relevant empirical studies conducted to compare the two theories in test development. Results: Findings reveals that CTT and IRT are highly comparable; however, no study provides enough empirical evidence on the extent of disparity between the two frameworks and the superiority of IRT over CTT despite the theoretical differences. Conclusion: the inability of these empirical studies to provide enough evidence of superiority of the IRT over CTT may result from the instruments they used in conducting the studies. It is recommended that further studies be conducted with different tools to further explore the true picture of the framework and provide enough evidences to justify or prove the theoretical stands of the two frameworks in the field of educational and psychological measurement.